Complete androgen insensitivity syndrome: factors influencing gonadal histology including germ cell pathology - Kaprova-Pleskacova, Jana; Stoop, Hans; Brüggenwirth, Hennie; Cools, Martine; Wolffenbuttel, Katja P; Drop, Stenvert L S; Snajderova, Marta; Lebl, Jan; Oosterhuis, J Wolter; Looijenga, Leendert H J (Modern pathology, 2014)
Patients with complete androgen insensitivity syndrome are at an increased risk for the development of gonadal germ cell cancer. Residual androgen receptor (AR) activity and abnormal gonadal location may influence the survival of atypical germ cells and the development of other histopathological features. To assess this, we evaluated 37 gonads from 19 patients with complete androgen insensitivity (ranging in age from 3 months to 18 years). Histological abnormalities were examined using hematoxylin and eosin-stained sections and sections stained for POU5F1 and KITLG, markers of early changes in germ cells at risk for malignant transformation. Hamartomatous nodules (HNs), Leydig cell hyperplasia (LCH), decreased germ cells, tubular atrophy and stromal fibrosis were more pronounced as age increased (P<0.001). Expected residual AR activity acted as a positive predictor only for non-malignant germ cell survival in (post)pubertal patients (P<0.05). Immunohistochemical studies indicated that delayed maturation of germ cells was present in three patients, whereas intermediate changes that occurred between delayed maturation and intratubular germ cell neoplasia, designated pre-intratubular germ cell neoplasia, were identified in four cases. Intratubular germ cell neoplasia was observed in one patient. Neither POU5F1 nor KITLG expression was dependent on expected residual AR activity. An independent effect of inguinal versus abdominal position of the gonads was difficult to assess because inguinal gonads were present primarily in the youngest individuals. In conclusion, many histological changes occur increasingly with age. Expected residual AR activity contributes to better survival of the general germ cell population in (post)pubertal age; however, it did not seem to have an important role in the survival of the germ cells at risk for malignant transformation (defined by POU5F1 positivity and KITLG overexpression) in complete androgen insensitivity. Comparison of the high percentage of patients in our study that were carrying germ cells with delayed maturation or pre-intratubular germ cell neoplasia with previously reported cumulative risk of tumor development in adult patients indicates that not all such precursor lesions in complete androgen insensitivity will progress to invasive germ cell cancer.
Keywords: mužské pohlaví; Male; Humans; testikulární nádory; kojenec; Testicular Neoplasms; lidé; Infant; mladiství; Child; dítě; Adolescent; testis; zárodečné buňky; Androgen-Insensitivity Syndrome; Neoplasms, Germ Cell and Embryonal; Testis; syndrom rezistence na androgeny; Child, Preschool; Germ Cells; předškolní dítě; germinální a embryonální nádory